Pembuatan Motion Graphic Sebagai Media Promosi Profil EO Batam Pos - Monika Pradila; Sandi Prasetyaningsih; Sonia Novi Rahman (Politeknik Negeri Batam, 2021)
Batam Pos Event Organizer (EO) is a professional event service provider and a part of PT. Sijori Interbintana Pers. Batam Pos EO, has not famous among people since Batam Pos is well-known by newspaper publisher. A media promotion is needed in order to give much more information to public. Research and development is used as a method to do a research in producing motion graphic. The result of this study ther media promotion can give information about Batam Pos EO effectively.